Convergence to the Rarefaction Wave for a Model of Radiating Gas in One-dimension - Huang, Fei-min; Li, Xing (Acta Mathematicae Applicatae Sinica, 2016)
In this paper, a sequence of solutions to the one-dimensional motion of a radiating gas are con- structed. Furthermore, when the absorption coefficient a tends to oo, the above solutions converge to the rarefaction wave, which is an elementary wave pattern of gas dynamics, with a convergence rate α -1/3｜lnα｜2.